The Influence of Dediphobia on Early Classroom Management in the Context of Islamic Religious Education - Ulpa Nurjanah Ulpa; Astuti Darmiyanti Astuti (Qoumun: Jurnal Pengabdian Masyarakat, 2025)
Effective character education for elementary school children focuses on intrinsic motivation rather than external fear. The phenomenon of "Dediphobia", which is a child's fear of external figures due to threatening stories, has become an important case study of the negative effects of extrinsic motivation that causes superficial obedience and can hinder psychological development. This study looks at the phenomenon of Dediphobia in the management of 1st grade elementary school, specifically in Islamic Religious Education (PAI), and how it impacts student discipline and psychological well-being. The study found that intrinsic motivation—based on autonomy, competence, and social connectedness—was far superior. This was achieved through the application of descriptive qualitative methodology with literature study. These results are in line with the principles of PAI which emphasize compassion, role models, and sincerity rather than violence. This shows how important it is to use a humanistic and safe classroom management approach, which encourages teachers and parents to be role models who instill values ​​through real knowledge and experience. The goal is to produce children who are disciplined, independent, and have noble character throughout life. Keywords: Intrinsic Motivation, Dediphobia, Islamic Religious Education, Classroom Management, Children's Character. Abstrak : Pendidikan karakter yang efektif untuk anak sekolah dasar berfokus pada dorongan intrinsik daripada ketakutan luar. Fenomena "Dediphobia", yang merupakan ketakutan anak figur di luar karena cerita ancaman, telah menjadi studi kasus penting tentang efek negatif dari motivasi ekstrinsik yang menyebabkan kepatuhan superfisial dan dapat menghambat perkembangan psikologis. Studi ini melihat fenomena Dediphobia dalam pengelolaan kelas 1 SD, khususnya dalam Pendidikan Agama Islam (PAI), dan bagaimana hal itu berdampak pada disiplin dan kesejahteraan psikologis siswa. Kajian ini menemukan bahwa motivasi intrinsik—yang didasarkan pada otonomi, kompetensi, dan keterhubungan sosial—jauh lebih unggul. Ini dicapai melalui penerapan metodologi kualitatif deskriptif dengan studi pustaka. Hasil ini sejalan dengan prinsip PAI yang menekankan kasih sayang, keteladanan, dan keikhlasan daripada kekerasan. Ini menunjukkan betapa pentingnya menggunakan pendekatan pengelolaan kelas yang humanis dan aman, yang mendorong guru dan orang tua untuk menjadi teladan yang menanamkan nilai melalui pengetahuan dan pengalaman nyata. Tujuannya adalah untuk menghasilkan anak yang disiplin, mandiri, dan berakhlak mulia sepanjang masa.   Kata Kunci: Motivasi Intrinsik, Dediphobia, Pendidikan Agama Islam, Pengelolaan Kelas, Karakter Anak.